2014
DOI: 10.1140/epjc/s10052-014-2975-3
|View full text |Cite
|
Sign up to set email alerts
|

Free energy of a Lovelock holographic superconductor

Abstract: We study thermodynamics of black hole solutions in Lanczos-Lovelock anti-de Sitter gravity in d + 1 dimensions coupled to nonlinear electrodynamics and a Stückelberg scalar field. This class of theories is used in the context of gauge/gravity duality to describe a hightemperature superconductor in d dimensions. A larger number of coupling constants in the gravitational side is necessary to widen the domain of validity of physical quantities in dual quantum field theory (QFT). We regularize the gravitational ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
(203 reference statements)
0
5
0
Order By: Relevance
“…In more than four dimensions higher order curvature terms are natural in Lovelock theory [6], and also higher order curvature corrections appear in the low-energy effective equations of Superstring Theory [7].The amount of published works in the literature reveals that Lovelock gravity is an exciting and active field. Black hole physics [8][9][10][11][12][13][14], cosmological solutions [15][16][17][18] and holographic superconductors exploiting the gauge/gravity duality [19] are some of the areas that have been explored in the framework of Lovelock gravity. However, the astrophysical implications of Lovelock theory should also be investigated.…”
mentioning
confidence: 99%
“…In more than four dimensions higher order curvature terms are natural in Lovelock theory [6], and also higher order curvature corrections appear in the low-energy effective equations of Superstring Theory [7].The amount of published works in the literature reveals that Lovelock gravity is an exciting and active field. Black hole physics [8][9][10][11][12][13][14], cosmological solutions [15][16][17][18] and holographic superconductors exploiting the gauge/gravity duality [19] are some of the areas that have been explored in the framework of Lovelock gravity. However, the astrophysical implications of Lovelock theory should also be investigated.…”
mentioning
confidence: 99%
“…Those symmetries were introduced in Refs.c [28,29,30,31,32,33,34] and can be regarded as generalizations of the so called Maxwell algebra [35,36], which describes the symmetries of quantum fields in Minkowski space with the presence of a constant electromagnetic field. Thus, for completeness and also due to the growing interest in the effect of higher-curvature terms in the holographic context (see for example [37,38,39,40]), in this work we will show that different Lovelock gravity actions in even dimensions can be obtained from a BI action based on the C m algebra. We shall start by considering the six-dimensional spacetime since it allows us to obtain a bigger variety of gravity theories.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, higher-curvature interaction in pure Lovelock gravity is also expected to show new features in a dual field theory. It has already been observed that there are holographic s-wave [27] and p-wave [28,29] phase transitions in a superconductor dual to higher-order gravity, such as Einstein-Gauss-Bonnet superconductor [30,31,32], and the field theories dual to quasitopological gravity [33,34], as well as Lovelock gravity [35,36]. Numerous work on this topic confirms that higher-order terms indeed have a notable effect on phase transitions, as they modify previously universal behavior of holographic theories.…”
Section: Introductionmentioning
confidence: 86%
“…Another important difference with respect to the backreaction noted in Ref. [35], is that the action needs scalar field counterterms when evaluated in the probe limit, since it becomes IR divergent. This counterterm is discussed in Ref.…”
Section: Holographic Phase Transitionmentioning
confidence: 99%